STRATEGI PENGEMBANGAN PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA (PPSNZJ) SEBAGAI PUSAT PEMASARAN PERIKANAN (Development Strategies of Nizam Zachman Jakarta Fishing Port as a Fish Market Center) - A. R. Sam; S. H. Wisudo; B. Murdiyanto; B. H. Iskandar (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2011)
Indonesia has signed Port State Agreement that initiated by Food Agriculture Organization (FAO), therefore some specified fishing ports including PPSNZJ should serve international ship well and safely. PPSNZJ, the biggest of fish market center, needs to prepare developing national and international marketing. Descriptive analysis was used to describe market activities in PPSNZJ, and SWOT analysis was used to obtain development strategy of PPSNZJ as a fish market center. The result showed that fish supply composition was 51,4% by fishing vessel landing in PPSNZJ and 48,6% by fish that transported into PPSNZJ. Share market of PPSNZJ consisted of export market (8,71%), domestic market (26,18%) and fish processing industry (65,11%). Development strategies of PPSNZJ as a fish market consisted of product strategy, facilities and infrastructure strategy and institutional strategy.Key words: development, fishing port, fish market center, strategy